Effect of spray process on dielectric properties of APS-deposited CaO–B2O3–SiO2 glass-ceramic coatings. Issue 13 (October 2020) - Li, Qi; Hu, Jing; Xie, Jianliang; Wang, Xin; Yu, Chengyong; Jiang, Shaoliang; Liu, Zhijie; Jiang, Xianyu; Sun, Chenli; Li, En; Deng, Longjiang
Abstract: Low-dielectric properties are highly desirable for successful realization of thermal spray coatings in electromagnetic wave absorption. Herein, CaO–B2 O3 –SiO2 (CBS) glass-ceramic coatings are prepared via high-enthalpy atmospheric plasma spraying (HE-APS) method, and the influence of spraying power on physical and dielectric properties of APS-deposited CBS coatings is systematically investigated. Under high-power conditions, the increase in liquid phase hinders the discharge of gases and leads to an increase in the porosity of CBS coatings. The experimental results reveal that the coating density decreases and coating porosity increases with the increase of spraying power. Based on the crystallization behavior of CBS coatings, an excellent low-dielectric crystalline phase (β-CaSiO3 ) was obtained after heat treatment at 800 °C. According to the dielectric mixing rule of composite materials, the density and permittivity exhibit the same trend and a minimum permittivity of 5.74 is obtained.